2021
DOI: 10.1155/2021/1718709
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Improves Cyclophosphamide-Induced Cystitis through TXNIP/NLRP3 and NF-κB Pathways

Abstract: Hemorrhagic cystitis is an important complication of cyclophosphamide chemotherapy, and current therapies for the disease are limited. The natural flavonoid luteolin (LUT) has significant anti-inflammatory and antioxidant properties, but its protective effect on cyclophosphamide (CYP)-induced bladder toxicity has yet to be evaluated. This study aims to explore the protective effect of LUT on CYP-induced acute cystitis in rats. Female Sprague-Dawley rats were randomly assigned to the control (CON) group, CON + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In this study, taxifolin's effects on the oxidative and inflammatory bladder damage caused by cyclophosphamide in rats were studied biochemically and histopathologically. The balance between the oxidant and antioxidant systems in cyclophosphamide-induced oxidative bladder injury has been studied previously [8]. The level of MDA was increased and the level of tGSH was decreased in the animals with cyclophosphamide-induced bladder tissue injury, according to Abraham et al [18].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, taxifolin's effects on the oxidative and inflammatory bladder damage caused by cyclophosphamide in rats were studied biochemically and histopathologically. The balance between the oxidant and antioxidant systems in cyclophosphamide-induced oxidative bladder injury has been studied previously [8]. The level of MDA was increased and the level of tGSH was decreased in the animals with cyclophosphamide-induced bladder tissue injury, according to Abraham et al [18].…”
Section: Discussionmentioning
confidence: 96%
“…The increase in the level of malondialdehyde (MDA), a result of lipid peroxidation (LPO), and the decrease in the level of the endogenous antioxidant glutathione (GSH) have been demonstrated to cause the toxic effects of cyclophosphamide on the bladder. It has also been suggested that cyclophosphamide-associated cystitis is associated with the expression of proinflammatory cytokines, such as nuclear factor-κB (NF-κB), tumor necrosis factor-alpha (TNF-α), interleukin 1 beta (IL-1β), and IL-6 [1,8]. According to evidence reported in the literature, antioxidant and anti-inflammatory medications may be beneficial in the treatment of cyclophosphamideinduced bladder injury.…”
Section: Introductionmentioning
confidence: 99%
“…23 Some evidence revealed that numerous flavonoids especially LUT and its analogs such as methoxyluteolin exhibit potent anti-inflammatory properties by repressing the NF-κB signaling pathway. [24][25][26][27] It has been reported that LUT decreased NF-κB activation at both the transcriptional and translational levels in various disorders, such as psoriasis, atopic diseases, diabetic cardiomyopathy, osteoarthritis, and toxicities. [28][29][30][31][32] So, it seems that NF-κB has been considered a pro-inflammatory signaling pathway and a target for new anti-inflammatory medications.…”
Section: Nf-κb Pathwaymentioning
confidence: 99%
“…Many agents disrupt the complex and activate the NF‐κB, including TNF‐α, IL‐1, ionizing radiation, and bacterial lipopolysaccharide (LPS) 23 . Some evidence revealed that numerous flavonoids especially LUT and its analogs such as methoxyluteolin exhibit potent anti‐inflammatory properties by repressing the NF‐κB signaling pathway 24–27 . It has been reported that LUT decreased NF‐κB activation at both the transcriptional and translational levels in various disorders, such as psoriasis, atopic diseases, diabetic cardiomyopathy, osteoarthritis, and toxicities 28–32 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that apigenin ( 1 ) administration blocks the secretion of pro-inflammatory cytokines and the activation of NF-κB; downregulates the expression of NLRP-3, TLR4, TNF-α, AMPK, and NF-κB; , and decreases the transcriptional activity of NF-κB and the phosphorylation of NF-κB, IκB, IKK, Lyn, Syk, MAPK, ERK, and JNK. , Similarly, luteolin ( 2 ) exerts an anti-inflammatory effect by downregulating the TLR4-mediated NF-κB/NLRP-3 and NF-κB phosphorylation. , The protective effects of acteoside ( 27 ) and isoacteoside ( 28 ) are mediated by phosphorylation of IKK, IκBα, NF-κB, and MAPK and the inactivation of TLR4-mediated NF-κB to modulate inflammation. , , Additionally, acteoside ( 27 ) restrains the inflammatory responses (TNF-α, IFN-γ, IL-6, and IL-12) by suppressing the JAK/STAT signaling pathway . Furthermore, plantamajoside ( 25 ) has anti-inflammatory properties via inhibition of the phosphorylation of IκBα, JNK, and MAPK, as well as nuclear translocation of NF-κB. , Unexpectedly, on the basis of the MAPK and NF-κB pathway, polysaccharides induce expression of MHC-II and CD86 to promote maturation of dendritic cells (DCs) and then accelerate the secretion of TNF-α and IL-12p70 so it may promote inflammatory effects .…”
Section: Biological Activities and Molecular Pharmacologymentioning
confidence: 99%